Analysis Of The Feasibility Of Organic Pesticides Tea Through The Assessment Of Financial And Non Financial Aspects: Case Study Of Business Of Monik B-Tea Students In Medan - Joko Susanto; Indra Fitriadi; Anggi Pradana; Monika Sutari (JASc (Journal of Agribusiness Sciences), 2019)
Utilization of agricultural products is one of the business opportunities for investors and entrepreneurs. Tea plantations are one of the leading commodities in Indonesia, where one of the producers is North Sumatra, which has three large tea gardens such as Toba Sari, Sidamanik, and Bah Butong. Utilization of tea is only limited to leaves, while tea seeds are not used which unknowingly have the benefit of being able to prevent Golden Snail pests in rice plants. So from that the need for a business that utilizes raw materials that are not worth being of economic value. Further studies and business feasibility studies need to be carried out to determine whether or not the business of organic tea pesticides is feasible in the city of Medan. This research is qualitative and quantitative, by collecting, and analyzing Monik B-Tea business financial data in Medan city. The results of the study can be determined that the results of the analysis show that the feasibility of organic fertilizer business when viewed from a non-financial aspect is feasible. From the technical, the production process uses simple techniques and equipment. From the market aspect, opportunities are still open due to high demand. And from the social aspects of the environment, organic pesticide businesses can contribute to the surrounding community. The analysis was carried out by the cash flow method, Payback Period, Benefit Cost Rational. The results of this analysis showed that the business of organic tea seed pesticides is feasible as shown by the positive final cash balance, the Payback Period which is smaller than the investment age, Cost Rational Benefit is greater than one.